Design and Development of High Speed Dry Cutting Database for Spiral Bevel Gear - Zhang Yu; Yan Hongzhi; Zeng Tao (Jixie chuandong)
The spiral bevel gear have the characteristics of design and processing parameters complexity.On the basis of a lot of high speed dry cutting technology parameters of the spiral bevel gear are collected and evaluated,based on the Microsoft SQL Server 2008 database development platform,the high speed dry cutting technology parameters database for spiral bevel gear is established and these parameters included machine tool,cutting tool,fixture,workpiece,and machining. The application program of database is developed based on Visual Basic 6. 0,and the basic functions of the database,such as query,add,modify,delete are realized.The spiral bevel gear processing required technical parameters can be rapidly obtained by this database system.It will play a significant role to improve the cutting efficiency and the machining quality,and reduce the processing cost.